Neurologic Manifestations as Initial Clinical Presentation of Familial Hemophagocytic Lymphohistiocytosis Type2 Due to PRF1 Mutation in Chinese Pediatric Patients - Feng, Wei-xing; Yang, Xin-ying; Li, Jiu-wei; Gong, Shuai; Wu, Yun; Zhang, Wei-hua; Han, Tong-li; Zhuo, Xiu-wei; Ding, Chang-hong; Fang, Fang (Frontiers in Genetics, 2020)
Familial hemophagocytic lymphohistiocytosis Type 2 (FHL2) associated central nervous system (CNS) involvement is less understood in children, especially when considering neurologic manifestations as part of the initial presentation. We conducted a retrospective review of the clinical manifestations and genetic abnormality of four Han Chinese children with FHL2 who were patients at the neurology department of Beijing Children's Hospital from November 2015 to October 2018. These four patients initially manifested CNS symptoms in their disease presentation, and all four patients were misdiagnosed as having ademyelinating disease, such as acute disseminated encephalomyelitis and multiple sclerosis. Given these misdiagnoses, it is important that general physicians and pediatricians maintain awareness of the possibility of FHL2 as a differential diagnosis. These four cases included neurologic manifestations including seizures, ataxia, spasticity, gait disorder, and coma. Abnormal signals bilaterally in the cerebrum, including in white matter, gray matter, and junctions were discovered. Enhanced magnetic resonance imaging (MRI) in these patients showed spot or ring enhancement and/or hemorrhage. These patients all possessed a compound heterozygote mutation PRF1 gene. Whole exome sequencing analysis revealed seven different mutations (three novel mutations) spread over the PRF1 gene and a heterozygous missense mutation c.1349C>T [p.T450M] that was present in two patients. Three novel mutations, c.634T>C[p.Y212H], c.1083_1094del[p.361_364del], and c.1306G>T [p.D436Y], were discovered, and through in silico analysis were discovered to be deleterious. Neurologic manifestations were the initial symptoms of FHL2 in these patients in addition to the expected leukopenia and hepatosplenomegaly. Whole exome sequencing of PRF1 for patients with similar presentations would facilitate prompt and accurate diagnosis and treatment.